Circulating Total and Active Metalloproteinase-9 and Tissue Inhibitor of Metalloproteinases-1 in Patients with Systemic Lupus Erythomatosus - Ewa Robak; Agnieszka Wierzbowska; Magdalena Chmiela; Liliana Kulczycka; Anna Sysa-Jedrejowska; Tadeusz Robak (Hindawi Limited, 2006)
We investigated the serum concentration of total metalloproteinase-9 (tMPP-9), active MMP-9 (aMMP-9), and tissue inhibitor of metalloproteinase-1 (TIMP-1) in a group of 41 patients with SLE and 20 healthy controls. Serum levels of tMMP-9 and TIMP-1 were assessed by an enzyme-linked immunosorbent assay (ELISA) and aMMP-9 by fluorometric assay. The tMMP-9 level was lower in SLE patients (mean 262 ng/mL) than in healthy volunteers (mean 325 ng/mL) (P=.048). Similarly, aMMP-9 level was lower in SLE patients (mean 121 ng/mL) than in control group (mean 169 ng/mL) (P=.0355) and lower in active SLE (mean 54 ng/mL) than in inactive disease (mean 99 ng/mL) (P=.033). TIMP-1 level was also lower in SLE patients (mean 181 ng/mL) than in control group (mean 233 ng/mL) (P=.004). In SLE patients, a positive correlation was found between tMMP-9 and aMMP-9 (ρ=0.568; P=.001). We also found a positive correlation of tMMP-9 and TIMP-1 with VEGF concentrations (ρ=0.450, P=.005 and ρ=0.387; P=.018, resp). tMMP-9, aMMP-9, and TIMP-1 serum levels are lower in SLE patients than in healthy control group.